Functional abnormalities in the primary orofacial sensorimotor cortex during speech in Parkinson's disease - Rektorova, Irena; Barrett, Jennifer; Mikl, Michal; Rektor, Ivan; Paus, Tomas (Movement disorders, 2007)
Parkinson's disease (PD) affects speech, including respiration, phonation, and articulation. We measured the blood oxygen level-dependent (BOLD) response to overt sentence reading in: (1) 9 treated female patients with mild to moderate PD (age; mean 66.0 +/- 11.6 years, mean levodopa equivalent 583.3 +/- 397.9 mg) and (2) 8 age-matched healthy female controls (age; mean 62.2 years +/- 12.3). Speech was recorded in the scanner to assess which brain regions underlie variations in the initiation and paralinguistic aspects (e.g., pitch, loudness, and rate) of speech production in the two groups. There were no differences in paralinguistic aspects of speech except for speech loudness; it was lower in PD patients compared with that in controls, when age was used as a covariate. In both groups, we observed increases in the BOLD response (reading-baseline) in brain regions involved in speech production and perception. In PD patients, as compared with controls, we found significantly higher BOLD signal in the right primary orofacial sensorimotor cortex and more robust correlations between the measured speech parameters and the BOLD response to reading, particularly, in the left primary orofacial sensorimotor cortex. These results might reflect compensatory mechanisms and/or treatment effects that take place in mild to moderately ill PD patients with quality of speech yet comparable with that of age-matched controls.
Keywords: řeč; mapování mozku; akustika řeči; Oxygen; Speech; magnetická rezonanční tomografie; Somatosensory Cortex; statistika jako téma; Aged; Case-Control Studies; Image Processing, Computer-Assisted; senioři; akustická stimulace; počítačové zpracování obrazu; Brain Mapping; lidé; kyslík; ženské pohlaví; studie případů a kontrol; Humans; Acoustic Stimulation; somatosenzorické korové centrum; Magnetic Resonance Imaging; Female; Parkinson Disease; Parkinsonova nemoc; Statistics as Topic; lidé středního věku; Speech Acoustics; Middle Aged